Integrasi Zakat Dalam Mendorong Keuangan Inklusif Di Indonesia - Aditya Yoga Kusuma; Dzakwan Fathurahman; Hendra Kurniawan; Muhammad Ihsan Jindy (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to analyze the strategic contribution of zakat management in strengthening inclusive financial structures and supporting a just socio-economic development agenda in Indonesia. This study uses a qualitative approach through a literature review of various scientific publications and policies related to zakat and inclusive finance. The goal is to analyze the strategic contribution of zakat management in strengthening inclusive financial structures and supporting a just socio-economic development agenda in Indonesia. Zakat plays a strategic role in promoting financial inclusion in Indonesia through a productive approach that empowers those entitled to receive zakat (mustahik), proven to improve welfare and reduce poverty. The integration of digital technology and Islamic fintech strengthens the efficiency and transparency of zakat management. However, challenges such as low zakat literacy and institutional limitations still need to be addressed. Cross-sector collaboration is key to maximizing zakat's role as an instrument for sustainable economic development and part of a just Islamic fiscal policy.